BRASIL NO SÉCULO XXI NA GEOPOLÍTICA DA CRISE: para onde apontam as utopias? - Alba Maria Pinho de Carvalho (Universidade Federal do Maranhão, 2016)
Set In the historical span of time of capital, at its structural crisis phase, this article discusses the current Brazilian insertion, placing it at the center of a critical evaluation. As part of a configuration including the crisis’ geopolitical circuits seen in the capital civilization of the XXI century, it is set as a background discussion that delineates positions and displacements within the world scenario. It evaluates, as its analytic focus, Brazil, as it promotes its economical adjustments that dominate the scene within tensions and democratic struggles. Within this perspective, it demarcates the country’s insertion in the finance-dominated capitalism encompassing adjustments cycles, and discuss policies adopted by the State in its accommodating role, seen along the late 25 years. It goes into “the chess game” of the Brazilian crisis by evaluating its organic attachment to the adjustment cycles that reveals the exhaustion of a rent-extract model and its tools of public income distribution to fight poverty. More specifically, it is the exhaustion of a “growing-with-inclusion” model associated to the Workers Party’s administration of the economy. Considering the crisis’ context and resumption of the orthodoxy of adjustment policies, resisting struggles raise the question of strong emancipating energies at a time of conservatism and attacks to the State by private entrepreneurs rallied in powerful lobbies. Analysis is closed, then, by the difficult choice faced by Brazilian contemporary leaders to propound utopias aimed at an emancipating perspective. Key words: Geopolitical crisis, brazilian contemporary, situation adjustment cycles, crisis, utopias. Recebido em: 16.03.2016. Aprovado em: 06.06.2016. 1 INTRODUÇÃO